CASE STUDY: ANALYSIS OF FOURTH GRADERS’ THINKING LEVELS ON ENGLISH VOCABULARY USING SMARTBOOK BASED ON BLOOM’S TAXONOMY - Jayanti, Sasti Nanda; Darmawan, Puguh (Transpublika Publisher, 2024)
The use of technology can serve as an attractive tool for students to enhance their abilities, one of which is by utilizing a smartbook that contains materials and practice questions packaged in various digital platforms. This article aims to identify the challenges students face in understanding English vocabulary based on Bloom's Taxonomy. Bloom's Taxonomy has been widely used as a reference to measure students' abilities in the learning process, particularly in the cognitive aspect. The method used in this research is qualitative with a case study approach. The respondents of this study were 7 students, the homeroom teacher, and the fourth-grade English teacher at SDN Sawojajar 6, Malang City. Data were collected through interviews and documentation. The results of the study indicate that students face challenges in solving medium to HOTS (Higher-Order Thinking Skills) level questions due to their low interest in learning English, limited use of gadgets at school, and unfamiliarity with HOTS-type questions in English subjects.